PENERAPAN PRINSIP TRANSPARANSI DALAM GOOD CORPORATE GOVERNANCE PADA PEMBIAYAAN MUDHARABAH MUQAYYADAH DI PT. BANK NEGARA INDONESIA SYARIAH CABANG PEKALONGAN - , ARY MAKRUM; , Destri Budi Nugraheni,S.H.,M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study entitled "The Implementation of the Transparency Principle In Good Corporate Governance On The Mudharabah Muqayyadah Financing at PT. Bank Negara Indonesia Sharia Pekalongan" aims to determine the implementation of the transparency principle of material and relevant information to customers as mudharib on mudharabah muqayyadah financing and to determine the implementation of transparency principle in implementing the decision making process by Islamic Bank on mudharabah muqayyadah financing in PT. Bank Negara Indonesia Sharia in Pekalongan This study uses empirical juridical approach. The datas used in this study are primary data and secondary data. The data were collected through field research by interview respondents and the research literature by way of study documents. This study used a non-probability sampling method and sampling techniques using purposive sampling method. The data obtained were analyzed by means of descriptive qualitative The results stated that the implementation transparency principle of the material and relevant information on the mudharabah muqayyadah financing in PT Bank Negara Indonesia Sharia in Pekalongan in the form of the provision of information which includes information on financing administrative requirements and information about the key points in the financing agreement with mudharabah muqayyadah scheme. Implementation of transparency principle in implementing the decision making process is realized through the provision of information about the stages that take place in the decision making process to provide mudharabah muqayaadah financing to potential customers. Besides transparency in the decision making process is openness the Islamic Bank to accept the opinions / suggestions / complaints from customers who influence the decisions taken by the Islamic Bank relating to mudharabah muqayyadah financing